Prospects for environmentally safe disinfection of urban sewerage with the help of compositions of non-toxic bactericidal metal complex reagents and surfactants - Tsivadze AYu; Fridman AYa; Barinov RA; Kruglina KA; Magomedrasul G (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
The prospects of environmentally safe disinfection of urban sewerage using compositions of bactericidal complexes of copper with amino acids and iminodiacetate derivatives of mucopolysaccharides and triglycerides of fatty acids are shown. When they are dosed into wastewater, the complexes penetrate into the structure of Suspended Particulate Matter (SPM) and mucus and within a few minutes bind the structural fragments of pathogens and larvae, which leads to their death with the outflow of cell fluid, the disappearance of fecal odor, cessation of putrification and coagulation of SPM. The complete disinfection is achieved at doses of complexes of 0.8 - 1.5 mmol per 1 kg of dry matter. The composition is dosed into sewage wells. Organo-mineral masses settle from disinfected wastewater. The use of compositions will reduce the negative impact of sewerage on the sanitary-epidemiological and ecological situation in settlements, increase the efficiency of existing treatment facilities and produce organo-mineral masses as commercial products.